Predictors of academics research performance and the significance of engaging in work activities - Mohd Rasdi, Roziah; Tauhed, Siti Zainab (Human Resource Management Academic Research Society, 2024)
Research activities and outputs play a significant role in determining the standing and performance of a university. This article aims to examine the influence of individual factors, work resources, and organizational factors on research performance, and the mediation effect of work engagement on these relationships among academics at four Malaysian research universities. Theory of personal engagement at work and job demands-resources theory were employed to explain academics’ research performance. The study utilized a cross-sectional design and surveyed 252 randomly selected academics. Individual effort and professional development were found to be significantly correlated to academics’ research performance, while organizational and work resources were not significantly associated with research performance. Work engagement did not mediate the relationships between all predictor variables and research performance. The study highlights the importance of individual factors and professional development in facilitating academics’ research performance and highlights the significance of human resource development in facilitating academics’ research performance.